Postgraduate Employment Outcomes of Undergraduate and Graduate Public Health Students: A Scoping Review. (November 2021) - Krasna, Heather; Gershuni, Olga; Sherrer, Kristy; Czabanowska, Katarzyna
Objectives: A key goal of schools and programs of public health is to prepare graduates for careers in the public health workforce after graduation, but are they achieving this goal? We assessed how the employment outcomes of students earning public health degrees are collected and described in the literature. Methods: Using the Kirkpatrick model of training evaluation as a framework, we conducted a 6-step scoping review: (1) formulating the research question, (2) identifying relevant studies, (3) selecting studies, (4) charting the data, (5) collating and summarizing the results, and (6) consulting stakeholders. We included articles published from January 1, 1993, through July 4, 2020, that provided data on employment status, employment sector/industry, job function, or salary of public health graduates. We excluded articles that were not written in English and were about dual-degree (ie, doctor of medicine–master of public health) students. We found and reviewed 630 articles. Results: We found 33 relevant articles. Most articles focused on a single school and combined multiple graduating classes, focused on subspecializations of public health, or focused on graduates' satisfaction with their curriculum but not employment outcomes. Data were inconsistently categorized, and studies were difficult to compare. Conclusions: Research on public health graduates' employment outcomes is scarce and does not follow consistent protocols. New standards should be adopted to systematize the collection of data on employment outcomes of public health graduates.